Applications of interferometric scattering microscopy (iSCAT) to single particle tracking in model and cell membranes - Reina, F (2018)
We have employed Interferometric Scattering (iSCAT) microscopy-based Single Particle Tracking (SPT) to study lipid dynamics of on model membranes and plasma membranes. This novel imaging technique offers high localization precision (~ 101 nm) and temporal resolution (< msec), together with tunable Signal-to-Noise Ratio. In the Materials and Methods, we describe our custom iSCAT setup. Also, an advanced analysis pipeline for SPT data is introduced, to estimate camera blurring and localization error effects in SPT data, and to statistically evaluate the most likely model of particle diffusion dynamics. In Chapter 3, we show the results of SPT experiments on gold nanoparticle-tagged lipids on model membranes. In slow sampling rate experiments (100Hz), the effects of localization error are not very pronounced, and vice versa in high sampling rate (2kHz) experiments. These experiments, corroborated by Fluorescence Correlation Spectroscopy (FCS) measurements, show that gold-tagged lipids are much slower compared to fl uorescent-dye tagged ones. This effect was attributed to the crosslinking potential and large size and of the gold tag. In Chapter 4, the effects of crosslinking are explored. Streptavidin and a monovalent version thereof ("Flavidin") are used to tag biotinylated lipids, and their dynamics analyzed through iSCAT-SPT and FCS. Both techniques show how tetravalent Streptavidin-tagged particles are ~ 2 times slower than Flavidin- tagged ones. Detection of 2 kDa polymer-conjugated lipids was also achieved with iSCAT. Chapter 5 is focused on the results of gold-tagged saturated lipids tracking on epithelial cell membranes. Their hopping diffusion behaviour was analyzed, and the diffusion in the confinement areas was found to be much slower than what previously reported. In conclusion, iSCAT-SPT is a very valuable technique in the study of mem- brane biophysics, which has helped us uncover some details on the effect of tag crosslinking, and promising details on the diffusion of lipids on cell membrane. Future developments in technology and analysis methodology will provide more insights in single molecule dynamics on membranes.